A new target for the old regulator: H‐NS suppress T6SS secretory protein EvpP, the major virulence factor in the fish pathogen Edwardsiella tarda. (12th September 2014) - Zhang, J.; Xiao, J.; Zhang, Y.; Cui, S.; Liu, Q.; Wang, Q.; Wu, H.; Zhang, Y.
Abstract The evpP gene in fish pathogen Edwardsiella tarda, coding the T6SS secretory protein EvpP and carrying an evpA‐evpO independent promoter region, was crucial for host cell invasion. The transcription of evpP was positively regulated by either the two‐component system EsrA‐EsrB or iron concentration, and its overexpression was known to enhance the invasion ability in our previous study. This work demonstrated that the H‐NS protein, a pleiotropic regulator of gene expression, was a new transcriptional modulator of evpP gene. The results showed that in vivo the transcriptional level of evpP was downregulated by H‐NS and in vitro this global regulator interacted directly with evpP promoter region. Moreover, DNase I footprinting experiments mapping the interaction regions of H‐NS and evpP revealed that this global regulator bound to evpP promoter and neighbouring areas at multiple sites. We provided a new insight into evpP regulation network and demonstrated the repression of H‐NS to the transcription of evpP gene. Significance and Impact of the Study Recently, the devastating fish disease edwardsiellosis caused by Edwardsiella tarda has been widely concerned. The xenogeneic silencing of the classic regulator H‐NS to the T6SS secretory protein EvpP, which played an important role in the virulence of Edw. tarda, was firstly reported in this study. It raised a better understanding of the virulence regulation of EvpP and provided more information about the complex infection mechanism of this pathogen. Our findings would contribute to the development of live attenuated vaccines against edwardsiellosis thus reducing the economic losses caused by this bacterium.